TRAINING AND ASSISTANCE IN WRITING TEACHING BOOKS, REFERENCE BOOKS AND MONOGRAPHS FOR LECTURERS - Khaeruman Khaeruman; Pramudi Harsono; Surachman Surachman; Tabroni Tabroni; Suflani Suflani; Abdul Bahits (Yayasan Education and Social Center, 2023)
Writing textbooks, reference books, and monographs is indeed one of the lecturers' efforts to improve their competence, especially in the academic field. This is caused by various factors, such as lack of available time, lack of experience and knowledge in writing, and lack of motivation and passion to complete writing projects. The service activities that you mentioned have a very important purpose to improve lecturers' understanding and skills in writing textbooks, reference books and monographs. The methods used, namely lectures, discussions, practicals, and direct assistance in the training room, are effective ways to achieve this goal. With the method of realization and implementation of community service activities carried out in 3 stages, namely the preparation stage, the training stage for writing books, and the monitoring and evaluation stage. This service activity was attended by 100 participants, consisting of lecturers from tertiary institutions, especially in Banten and participants who have successfully completed their book drafts. Although the participants were very enthusiastic about participating in this activity, only a few participants managed to complete their book drafts. However, the results obtained from this community service activity remained positive, namely the participants were able to publish a book with an ISBN. This shows that this service activity provides good benefits in increasing participants' understanding and skills in writing textbooks, reference books, and monographs. The participants wanted further training and intensive assistance to produce a book that was ready to be published